Recent Advances in Optimization Design and Performance Analysis of Vortex Pumps - Wang, Yang; Zhou, Peijian; Xu, Naijiang; Zhou, Wenqiang; Li, Jian (Recent Patents on Mechanical Engineering, 2023)
Background: The vortex pump is a type of sewage pump renowned for its non-clogging performance. As the vortex pump has a special structure type, there are many vortex structures in the volute and impeller flow channel, which reduce the efficiency of the vortex pump. Reducing the energy loss and improving the efficiency of the vortex pump has been one of the main research objectives of designers. In this paper, the research progress of vortex pumps is summarized from the two aspects of transporting solid medium and low efficiency, which can provide a reference for future research. Methods: The latest patents and papers on vortex pumps were collected. The solid-liquid flow characteristics from the experimental and numerical perspectives, the influence of geometric parameters on external characteristics, and optimization design methods of the vortex pump were studied. Results: The particles, fibers, and cloth in the vortex pump will become trapped and blocked in the cavity. And the geometric parameters have an obvious effect on the pump. By using the intelligent optimization algorithm to optimize the impeller parameters, the pump efficiency can be increased by 10.25% under large flow conditions and the effective blade shear stress. Conclusion: The concentration and diameter of particles could change the performance of the pump. The retention and plugging of the solid medium in the vortex pump are related to flow structure and backflow. Appropriate geometric parameters should be selected when designing a vortex pump. Too large or too small a structure design will lead to poor performance of the vortex pump. This can be combined with intelligent optimization algorithms for pump design, which is a very effective method.
Keywords: Optimal design